Gallery of honour of Dutch photography - Donker, Birgit 1965-; Gierstberg, Frits 1959-; Harrevelt, Loes van (Lecturis, 2021)
This book is comprised of almost 100 photographs, each remarkably special in terms of artistic, aesthetic, and social qualities. Together the images tell the story of 180 years of photography in the Netherlands and its colonies, from 19th-century daguerreotypes to contemporary works by Rineke Dijkstra, Dustin Thierry, Bertien van Manen, Dana Lixenberg, Lee To Sang, and more. Compiled for the Nederlands Fotomuseum by a committee of five experts, the selected images display the richness of the work of photographers who explore the borders of the medium and are unafraid to challenge them. Encompassing numerous narratives, the photographs also show how radically the technology and sociocultural function of photography has evolved.00Exhibition: Nederlands Fotomuseum, Rotterdam, The Netherlands (postponed)
This publication appeared in relation to the Gallery of honour of Dutch photography in the Netherlands Fotomuseums from 20 January 2021 onwards
Keywords: Geschichte 1842-2021; Fotografie; Niederlande; Ausstellungskatalog -- Nederlands Fotomuseum -- 20.01.2021- -- Rotterdam; Bildband